Calcium Binding Protein S100A16 Expedites Proliferation, Invasion and Epithelial-Mesenchymal Transition Process in Gastric Cancer - Xiaoying You; Min Li; Hongwei Cai; Hongwei Cai; Wenwen Zhang; Ye Hong; Wenjie Gao; Yun Liu; Xiubin Liang; Tijun Wu; Fang Chen; Dongming Su; et al. (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer (GC) is one of the most common malignant tumors of the digestive system, listed as the second cause of cancer-related deaths worldwide. S100 Calcium Binding Protein A16 (S100A16) is an acidic calcium-binding protein associated with several types of tumor progression. However, the function of S100A16 in GC is still not very clear. In this study, we analyzed S100A16 expression with the GEPIA database and the UALCAN cancer database. Meanwhile, 100 clinical GC samples were used for the evaluation of its role in the prognostic analysis. We found that S100A16 is significantly upregulated in GC tissues and closely correlated with poor prognosis in GC patients. Functional studies reveal that S100A16 overexpression triggers GC cell proliferation and migration both in vivo and in vitro; by contrast, S100A16 knockdown restricts the speed of GC cell growth and mobility. Proteomic analysis results reveal a large S100A16 interactome, which includes ZO-2 (Zonula Occludens-2), a master regulator of cell-to-cell tight junctions. Mechanistic assay results indicate that excessive S100A16 instigates GC cell invasion, migration, and epithelial-mesenchymal transition (EMT) via ZO-2 inhibition, which arose from S100A16-mediated ZO-2 ubiquitination and degradation. Our results not only reveal that S100A16 is a promising candidate biomarker in GC early diagnosis and prediction of metastasis, but also establish the therapeutic importance of targeting S100A16 to prevent ZO-2 loss and suppress GC metastasis and progression.